Investigation of the Challenges of Public Education Centre Instructors - Esen Altunay; Evrim Erol (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Alternative education opportunities are needed outside of formal education institutions to train individuals, develop skills, and sustain lifelong learning. Adult Education Centres, which have a priority and predominant position among institutions that support lifelong learning in Türkiye, are among the leading institutions that help individuals’ personal, professional, and social development. For this reason, identifying and solving the challenges of Adult Education Centres instructors positively contributes to the quality and traceability of adult education. In this context, the study aims to determine the opinions of adult instructors in Adult Education Centres about their challenges and to develop suggestions based on the findings. For this purpose, to obtain in-depth information about the challenges of adult instructors in Adult Education Centres, the phenomenology design, one of the qualitative research methods, was preferred in the study, and the study group was formed from thirty-six participants determined by maximum diversity sampling, one of the purpose sampling techniques. The research data were collected with a semi-structured interview form. According to the findings, the challenges of the instructors were in the themes of institutional challenges, professional challenges, and trainee challenges; trainers’ approaches to coping with problems were in the themes of the support-seeking approach, the planned approach, and the reactive approach; Adult Education Centres directors’ approaches to the challenges of trainers have gathered the themes of the supportive and insensitive approach. When the results of the study are evaluated collectively, the Adult Education Centres should create institutional solution strategies for the problems of the instructors; It is recommended that the trainers be employed permanently, that the unfavourable conditions they work in are corrected and that the psychological and social, technological, and physical support they need is provided.